The Realization of Genre Analysis on Students’ Essay: A Classroom Discourse Perspective - Yusuf Hidayat; Ani Herniawati (Journal Corner of Education, Linguistics, and Literature, 2023)
Discourse analysis area becomes an essential issue in teaching and learning English in Indonesia. Through applying this approach, the lecturer as the researcher can analyze the students’ texts written during their writing course. This study was aimed at reporting the realization of genre analysis on students’ essay. Through employing discourse analysis approach, the writers selected 3 essays written by the freshmen from the Early Childhood Education Department, Islamic College of Putra Galuh Ciamis. In analyzing the texts, the writers employed context of culture or as the so-called ‘genre analysis’ to determine the social function, generic structure, and linguistics feature of the selected essays. In this study, the writer then addressed 3 research questions: (1) How is the social function of the texts realized? (2) How is the generic structure of the texts realized? (3) How is the linguistics feature of the texts realized? The findings of the study revealed that the realization of the social function of the essays is retelling past events for the purpose of informing or entertaining which was shown by the title of the text. The first essay entitled: “Student’s Skill Competition”, the second essay entitled: “Visiting My Grandmothers’ House”, and the third essay entitled: “Holiday in Pangandaran Beach”. Meanwhile, the realization of the generic structure covered: (a) introduction which tells orientation, (b) sequence of events which tells the events in the order they occurred, and (c) a conclusion which tells re-orientation. Moreover, the realization of the linguistics feature focused on (a) specific participants, (b) the use of past tense, (c) the use of material process and circumstances of time and place. In conclusion, dealing with the social function, generic structure, and the linguistics feature realized on the whole essays, the whole analyzed essays were categorized as recount texts.